Particle characterization and composition in the NE Aegean Sea: Combining optical methods and biogeochemical parameters. (1st October 2017) - Karageorgis, A.P.; Drakopoulos, P.G.; Psarra, S.; Pagou, K.; Krasakopoulou, E.; Banks, A.C.; Velaoras, D.; Spyridakis, N.; Papathanassiou, E.
Abstract: The NE Aegean Sea constitutes a challenging sector of the world ocean in studying optical and biogeochemical properties and processes due to a dynamic frontal regime resulting from the continuous mixing of Black Sea waters (BSW) and waters of Levantine origin (LW), which are characterized by substantially different physical, chemical and biological properties. In the framework of Perseus and AegeanMarTech projects, inherent optical properties (IOPs; beam attenuation, optical backscattering, chlorophyll- α fluorescence), particle size, and discrete bottle data (particulate matter, particulate organic carbon, and chlorophyll- α concentrations) were measured during October 2013, March and July 2014. Black Sea water enters into the Aegean Sea through the Dardanelles and disperses to the west-northwest, as traced by characteristic salinity minima. The core of the BSW to the east of Lemnos Island was occasionally particle-enriched, showing maxima in c p, b bp, D 50, PMC, POC, and TChl- α, the latter, however, detected primarily at sub-surface layers. Particle composition was chiefly organic, associated with phytoplanktonic communities (BSW and LW), heterotrophic planktonic organisms and detrital organic matter primarily originating in the BSW and forming aggregates often >100 µm in diameter. A discrepancy between particle and TChl- α abundance was observed, with c p local maxima occurring in surface waters (BSW) and TChl- α maxima in mid-waters (LW). This pattern was attributed to phytoplankton photo- acclimation with depth leading to increased cell- chlorophyll content deeper, not necessarily matched by a similar biomass increase, thus, using TChl- α as an absolute proxy for phytoplankton biomass may not be appropriate, when considering water bodies encompassing the entire euphotic zone. Primarily in surface waters, the in situ optically measured median particle diameter primarily corresponds to large particles/aggregates, contrary to the findings obtained by laboratory analysis of cell counts in discrete water samples; this inconsistency was attributed to the fragile nature of aggregates that usually break up during sample processing and other methodological issues. The particulate backscattering ratio as well as the estimated bulk particulate index of refraction revealed a 2-layer structure, with biogenic particles and organic detritus occupying the upper ~65 m of the water column, whereas deeper waters were enriched in lithogenic/organic particles resuspended from the seabed. Overall, the NE Aegean Sea is characterized by low particulate matter concentrations and low chlorophyll biomass during the sampling periods, exhibiting rather open-sea characteristics, reflected on all optical properties studied, as evidenced by their very low values and also by the POC: c p regression parameters. The present work contributes to a better understanding of bio-optical properties of the Aegean Sea, which by extension may improve regional satellite algorithms applied to retrieve chlorophyll- α concentration from space. Highlights: IOPs accompanied by biogeochemical bottle data were measured in the NE Aegean Sea. The NE Aegean sea exhibits IOP ranges comparable to the open ocean. Aggregates often >100 µm in diameter were abundant in the Black Sea water layer (BSW). In the surface BSW layer the majority of POC is not related to new autotrophic production but rather to the input of organic detritus. Due to phytoplankton photo- acclimation with depth, we observed increased cell- chlorophyll content at mid-water depths, not necessarily matched by a similar biomass increase.